Molecular basis of metabolic reprogramming in innate immune cells: impact of drugs on the mitochondrial function - Xelwa, Ntombikayise Hendrietta Marcia (My University, 2016)
This study focused on reprogramming of energy metabolism of cancer cells, since most cancer and proliferating cells have been shown to display a metabolic shift by displaying increased dependence on glycolysis and reduced oxidative phosphorylation (OXPHOS) for energy. Dichloroacetate (DCA) and Methyl pyruvate (MP) were used to attempt the reversal of the metabolic program of THP-1 cells. Flow cytometry was used to determine the mode of cell death and to analyse the changes in cell cycle. In this study, an overexpression of TLR4 was observed in THP-1 cells treated with 5ng/ml of lipopolysaccharides (LPS). Further analysis of cell death showed that MP and DCA-treated cells resulted to minimal induction of apoptotic cell death. This suggests that the 2 drugs (MP and DCA) cause cell death via apoptosis. Furthermore, LPS treated cells (infected cancer cells) showed an increase in glycolysis (Warburg effect). This study has shown that indeed treatment with drugs such as MP and DCA was effective in reversing the glycolytic phenotype of THP-1 cells, resulting in cell death via apoptosis by boosting OXPHOS.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulfillment of the requirements for the degree of Masters of Science 2016
Keywords: Apoptosis; Mitochondrial pathology; Cancer cells